Assessment of the Integrated Approach to Disease Surveillance in East Akim Municpality of the Eastern Region - Adjabeng, M.JDJABENG (My University, 2008)
Integrated Disease Surveillance and Response (IDSR) aims at integrating surveillance functions at all levels. Ghana as a country decided on 23 communicable diseases and conditions to be targeted as priority diseases for surveillance using the integrated approach. A qualitative research was conducted to assess the effectiveness of the integrated approach to disease surveillance and response strategy in East Akim Municipality of the Eastern Region. A total of twenty (20) key respondents were purposively selected from the various administrative levels of the health system. An in-depth interview and review of records were the main methods employed for data collection. The strategy of integrating disease surveillance activities was perceived differently depending on the administrative level of operation. Other important aspects of what integration meant were left out from the responses given; thus ‗collecting information from a single focal point‘, ‗linking data to analysis and response mechanism‘, and ‗responding with the most effective public health intervention‘. Laboratory involvement in disease surveillance was acknowledged as very important and their roles very effective in facilitating IDSR. From the comments received, the IDSR system is not simple. The flexibility could be described as low as it depended on too many factors from respondents‘ view point which are not readily available or feasible. Acceptability is quite high with regards to participation by other stakeholders, especially the WHO, QHP, UNICEF and most importantly by the community (CBSVs). The private sector participation has not been fully explored. Most respondents further indicated in outright terms that they were not pleased with the current surveillance system and reasons were largely attributed to lack of funds to carry out surveillance activities. Much of the data remains unprocessed, or if processed, unanalyzed, or if analyzed, not read, or, if read, not used or acted upon. If the researcher is to take the measuring scale of one of the respondents and score the integration approach as a strategy within disease surveillance, a score of four (4) would be awarded on a scale of one (1) to ten (10) where ten is the highest. The development of human resource is essential in implementing recommendations made to improve IDSR. Reporting systems of diseases should be evaluated more frequently and decision made to improve on service delivery.
Keywords: ASSESSMENT; INTEGRATED APPROACH; DISEASE SURVEILLANCE; EAST AKIM MUNICPALITY; EASTERN REGION